NephroTalk Multimodal Conservative Care Curriculum for Nephrology Fellows. Issue 6 (June 2021) - Cohen, Robert A.; Bursic, Alexandra; Chan, Emily; Norman, Marie K.; Arnold, Robert M.; Schell, Jane O.
Abstract : Conservative care, a comprehensive treatment path for advanced kidney disease most suitable for individuals unlikely to benefit from dialysis, is underutilized in the United States. One reason is an absence of robust education about this approach and how to discuss it with potential candidates. To address this need, we developed a multimodal conservative care curriculum for nephrology fellows. This curriculum consists of four online modules that address essential concepts and communication skills related to conservative care. It is followed by an in-person, interactive, "flipped classroom" session facilitated by designated nephrology educators at participating Accreditation Council for Graduate Medical Education nephrology training programs. Curriculum effect was assessed using surveys completed by participating fellows immediately before and following the curriculum and for participating nephrology educators following flipped classroom teaching; 148 nephrology trainees from 19 programs participated, with 108 completing both pre- and postcurriculum surveys. Mean self-reported preparedness (measured on a five-point Likert scale) increased significantly for all ten concepts taught in the curriculum. The mean correct score on eight knowledge questions increased from 69% to 82% following the curriculum ( P <0.001). Fellows rated the curriculum highly and reported that they plan to practice skills learned. For the 19 nephrology program educators, the mean perceived preparedness to teach all curriculum domains increased after, compared with before, facilitating the flipped classroom, reaching significance for seven of the ten concepts measured. Data suggest that fellows' participation in a multimodal curriculum increased knowledge and preparation for fundamental conservative care concepts and communication skills. Fellows rated the curriculum highly. Educator participation appears to have increased preparedness for teaching the curriculum concepts, making it likely that future education in conservative care will become more widespread. Herein, we describe the curriculum content, which we have made publicly available in order to encourage broader implementation, and its effect on participating fellows and the nephrology educators who facilitated it.